PENERAPAN PEMBERIAN KOMBINASI MINT (PAPPERMINT OIL) DAN CAIRAN DENGAN NEBULIZER PADA PASIEN DENGAN BATUK ASMA BRONCHIALE DI RSUD UNGARAN - Ainnur Rahmanti; Ixrofiatul Muarifah (Jurnal Kesehatan Medika Udayana, 2020)
Asthma Bronchiale is inflammation in the airways (bronchi) where excessive lung mucus production makes breathing difficult. One treatment that can be given is by giving nebulizer therapy to ease the cough response to the presence of mucus in the respiratory tract with the addition of mint oil. The purpose of the case study is to illustrate the effect of adding mint (pappermint oil) and liquid with a nebulizer on the handling of asthma bronchiale cough in Ungaran District Hospital. The subject of this case study used two patients with asthma bronchiale, willing to be investigated, cooperative and more than 5 years old. Data was collected by observation and administration of nebulizer therapy by adding pappermint oil and liquid using a nebulizer. The results of the case study found that subject I had a cough frequency of 25 (moderate), no inflammation, no wheezing and easy sputum discharge, whereas in subject II the frequency of cough became 24 (moderate), no inflammation, no wheezing, and easy phlegm Exit. This study is recommended to apply pappermint oil therapy to reduce the frequency of cough bronchial asthma patients